Conditions in occupational therapy : effect on occupational performance - Atchison, Ben; Dirette, Diane Powers (Philadelphia : Wolters Kluwer, 2017)
"This book reflects the most current research and brings in 5 new chapters covering conditions your students will see in practice. This with new features and tools further help enhance this essential book. Each chapter follows a consistent format--an opening case, followed by definition and descriptions, incidence and prevalence, signs and symptoms, course and prognosis, medical/surgical management, impact on occupational performance, and finally, two case illustrations."--Publisher
Thinking like an OT -- Cerebral palsy -- Autism spectrum disorders -- Intellectual disability -- Muscular dystrophy -- Attention deficit disorder -- Sensory processing disorder -- Mood disorders -- Schizophrenia and other psychotic disorders -- Anxiety disorders -- Neurocognitive disorders -- Complex trauma -- Obsessive-compulsive and related disorders -- Somatic symptoms and related disorders -- Feeding and eating disorders -- Substance-related and addictive disorders -- Cerebrovascular accident -- Cardiopulmonary disorders -- Diabetes -- Acquired brain injury -- Burns -- Progressive neurodegenerative disorders -- Rheumatic diseases -- Spinal cord injury -- Orthopedics -- Low vision disorders -- Cancer -- Obesity
Includes bibliographical references and index
1 13
Keywords: Occupational therapy; Occupational therapy -- Case studies